An Integrated Test for Electoral Cycles in the U.S. Economy - Haynes, Stephen E.; Stone, Joe A. (The Review of Economics and Statistics, 1989)
This paper offers the first integrated test of the electoral model of business cycles. The test begins with unrestricted estimates of presidential electoral patterns in U.S. economic outcomes (real GNP, unemployment, and inflation) and policies (money growth and the adjusted budget surplus). These estimates are then used to determine whether the estimated electoral patterns in macropolicy yield predicted electoral patterns for macro outcomes that are consistent with estimates of both actual electoral patterns in outcomes and voting behavior. The results indicate that four-year electoral cycles in macroeconomic outcomes and policies are strongly significant for the United States for the period 1951I to 1986II. Copyright 1989 by MIT Press.